FEEDING IN THE ORGANIZED CHILDREN COLLECTIVES AND ITS IMPACT ON THE PHYSICAL GROWTH AND CAPACITY FOR WORK OF THE CHILDREN AGED 6 - T.Yu. Vishnevetskaya; Zh.Yu. Gorelova; A.Yu. Makarova (Вопросы современной педиатрии, 2007)
The authors carried on the study with regards to the feeding, which the preschool children received in the 1141st preschool educational institution. The study of 123 children aged 6 provided the findings in the areas of the physical growth and capacity for work. The average and upper average levels of the physical capacity for work were disclosed among 60–74% of the examined children irrespective of the biomaturity rates and among 86% of children with harmonious and even among 67% of children with disharmonious morpho-functional status.Key words: feeding, physical growth, physical capacity for work, preschool children.